Preoperative prediction of flexible ureteroscopy outcome in the treatment of renal calculi - Mohammed Abozaid; Eid Elsherif; Fatma Elserafy; Islam Abobakr; Mohamed Selim (African Journal of Urology)
Abstract Background Retrograde intrarenal surgery (RIRS) is increasingly used for management of renal calculi. Many predictive scores have been devised to predict stone-free rate (SFR) after RIRS including Ito’s nomogram. The aim of this study is to evaluate preoperative parameters that affect SFR after RIRS to help with patient counselling. Methods Patients with renal stones up to 30 mm in greatest diameter were recruited. They were offered RIRS via disposable flexible ureteroscopy and Holmium laser fragmentation. Ito’s score was calculated for each patient preoperatively to estimate post-operative SFR. Also, other factors as stone Hounsfield units (HU), pre-stenting, and access sheath use were recorded. Results A total of 80 patients met the inclusion criteria. Median stone volume was smaller in cases that were stone free (532.4 vs 748.0 mm3, p = 0.076). Patients with residuals had higher rates of multiple (61.5% vs 16.7%, p < 0.001) and lower pole (61.5%vs 37.0%, p = 0.039) calculi. Hydronephrosis, operator experience, HU, access sheath use, pre-stenting, and total Ito score were not significantly different between stone-free patients and patients with residuals. Multivariate logistic regression showed that presence of multiple renal stones (B = 0.158, p = 0.002) is the only significant predictor of SFR. Conclusion Larger stones, stones in the lower pole, and especially multiple renal stones have higher rates of residual stones after RIRS. This should be clarified to patients during preoperative decision-making and discussion about RIRS and its alternatives’ pros and cons has to take place prior to surgery. Trial registration: Trial registered at clinicaltrial.gov, under number NCT05857501 on May 10th, 2023. https://clinicaltrials.gov/study/NCT05857501 .